2020
DOI: 10.1177/2066220320980870
|View full text |Cite
|
Sign up to set email alerts
|

Examining the policies of paroling authorities in the United States to support evidence-based practices

Abstract: While much research in community corrections examines ways in which direct supervision can reduce recidivism, less is known about the role of paroling authorities in using or supporting evidence-based practices. This study presents a selection of results from a survey of paroling authorities across the United States conducted in 2015. We analyze and discuss survey results on the following three topics: (1) What is the structure and power/authority of the paroling authorities? (2) What are the appointments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 30 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Like Alexis, Mina worried that the parole board would not take her seriously because she is a "habitual offender." This finding is unsurprising as prior research found that criminal offense severity influences parole decisions (Caplan, 2007;Connor, 2016;Harbinson & Ruhland, 2020;Tewksbury & Connor, 2012). In contrast, Kayla, a woman who did not believe her convictions would impact the parole board's decision, felt so because her offense was not a very serious or violent crime.…”
Section: Feelings Throughout the Processmentioning
confidence: 89%
See 4 more Smart Citations
“…Like Alexis, Mina worried that the parole board would not take her seriously because she is a "habitual offender." This finding is unsurprising as prior research found that criminal offense severity influences parole decisions (Caplan, 2007;Connor, 2016;Harbinson & Ruhland, 2020;Tewksbury & Connor, 2012). In contrast, Kayla, a woman who did not believe her convictions would impact the parole board's decision, felt so because her offense was not a very serious or violent crime.…”
Section: Feelings Throughout the Processmentioning
confidence: 89%
“…Other responses included completing your requirements, having support, building a reentry plan, mentally preparing, and reviewing documents (i.e., PSI and police report). Much of the women's advice aligns with factors considered influential in parole hearings (Caplan, 2007;Connor, 2016;Harbinson & Ruhland, 2020;Lavin-Loucks & Levan, 2018;Tewksbury & Connor, 2012;West-Smith et al, 2000). Most importantly, these findings should be shared with parole-seeking women and individuals working with them, and methods of doing so are discussed in the implications.…”
Section: Advice For Future Parole-seeking Womenmentioning
confidence: 97%
See 3 more Smart Citations